The Effect of Transfer Pricing and Other Factors on Tax Aggressiveness - Taji, Putri Cahyaningtyas Sekar; Palupi, Agustin (Journal of Islamic Contemporary Accounting and Business, 2024)
This research was conducted with the aim of obtaining empirical evidence regarding the effect of transfer pricing, capital intensity, inventory intensity, profitability, leverage, liquidity, and firm size on tax aggressiveness. This type of research is quantitative research using secondary data sources obtained from the company's financial statements. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2021 period. In this study, the sampling technique used was the purposive sampling method with 6 predetermined research criteria so that a total sample of 47 companies or 141 research data was obtained. The data analysis technique in this study used multiple regression analysis to test the hypothesis using the SPSS 25 application. The results of the analysis of this study indicate that the variable profitability has a significant negative effect on tax aggressiveness and firm size has a significant positive effect on tax aggressiveness. Meanwhile, transfer pricing, capital intensity, inventory intensity, leverage and liquidity have no effect on tax aggressiveness.